The Perception of Natural and Modulated Movement Sounds. (August 2014) - Kennel, Christian; Pizzera, Alexandra; Hohmann, Tanja; Schubotz, Ricarda Ines; Murgia, Mauro; Agostini, Tiziano; Raab, Markus
The motor system is engaged when we perceive movement in the environment, even when we have no sensorimotor experience of that movement. It has been suggested that this ability relies on internal models that comprise specific exteroceptive representations, such as audition and vision. It has been shown that, for human movements, the quality of perception depends on the closeness between the perceived movement and the perceiver's own capability of reproducing it. Thus, if we are able to reproduce a movement, we also have the interoceptive motor memories that enable us to run internal models and perceive the same movements more accurately when merely observed. In a behavioral study we investigated if participants would be able to distinguish between self-produced and other-produced movement sounds from a previously recorded hurdling performance. We also analyzed if participants' discriminative ability would vary as a function of specific sound features, examining rhythmic step structure and amplitude range. The results reveal that participants were able to distinguish between their own and others' movement sounds. However, changing either rhythmic step structure or amplitude range of the sounds did not influence this self-other discrimination. We suggest that identification of one's own movement sounds is holistically achieved as an auditory gestalt.